Prevalencia de vida y factores asociados al consumo de marihuana en estudiantes escolarizados de Pamplona, Colombia, durante el primer periodo de 2015: Estudio Emtamplona - Martínez-Torres, Javier; Rangel-Navia, Heriberto; Rivera Capacho, Eliana Elizabeth (Revista Médica de Chile, 2018)
Background: Obesity is associated with pain, reduction of function and quality of life in patients with osteoarthritis (OA). Aim: To describe the clinical profile of women with knee OA according to their body mass index (BMI). Material and methods: Observational study in 308 women with knee OA. According to their BMI, they were classified as normal-weight, overweight and obese. The primary outcome measure was functionality evaluated with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Secondary outcomes were sleep quality evaluated using the Pittsburgh Sleep Quality Index (PSQI) and quality of life assessed with the European Quality of Life Five Dimension Five Level Scale (EuroQol-5D). Results: WOMAC, PSQI and EuroQol-5D scores were significantly higher in obese women. Conclusions: Overweight and obese women with OA have more sleep disorders, reduction on functionality and quality of life compared to their normal weight counterparts.